Modeling of reliability characteristics typically assumes that components and systems fail if a certain individual damagelevel is exceeded. Every (mechanical) system damage increases irreversibly due to employed loading and (mechanical)stress, respectively. The main issue of damage estimation is adequate determination of the actual state-of-damage. Severalmathematical modeling approaches are known in the literature, focusing on the task of how loading effects damageprogression (e.g., W¨ohler, 1870) for wear processes. Those models are only valid for specific loading conditions, a prioriassumptions, set points, etc. This contribution proposes a general model, covering adequately the deterioration of a setof comparable systems under comparable loading. The main goal of this contribution is to derive the loading?damageconnection directly from observation without assuming any damage models at the outset. Moreover, the connection is notinvestigated in detail (e.g., to examine the changes in material, etc.) but only approximated with a probabilistic approach.The idea is subdivided into two phases: A problem-specific relation between loading applied (to a structure, which contributesto the stress) and failure is derived from simulation, where a probabilistic approach only assumes a distributionfunction. Subsequently, an adequate general model is set up to describe deterioration progression. The scheme will beshown through simulation-based results and can be used for estimation of the remaining useful life and predictive maintenance/control.Keywords: reliability, parameter estimation, damage accumulation, probabilistic simulation. - Dettmann, Kai-Uwe; Söffker, Dirk (Zielona Góra: Uniwersytet Zielonogórski)
Modeling of reliability characteristics typically assumes that components and systems fail if a certain individual damage level is exceeded. Every (mechanical) system damage increases irreversibly due to employed loading and (mechanical) stress, respectively. The main issue of damage estimation is adequate determination of the actual state-of-damage. Several mathematical modeling approaches are known in the literature, focusing on the task of how loading effects damage progression (e.g., W¨ohler, 1870) for wear processes
Keywords: reliability; parameter estimation; damage accumulation; probabilistic simulation